Where archaeology and history meet; historical-archaeological research after the try-house of Hoorn in Smeerenburg on Spitsbergen (Bulletin KNOB, 1990)
Striving after l'histoire totale, which describes all expressions of human life historians make use of representations (iconography) and inventories. The object itself however is studied by archaeologists and historians of art most of the social historians mainly considering the object an illustration. Still the historian's method strongly resembles the archaeologist's. The archaeologist studies artefacts to comprehend daily life in the past as well as the social stratification of a certain period. Both sciences could serve one another, history relating material archaeological data to 'historical reality' created by means of written accounts.The project in Smeerenburg which has been executed by the Arctic Centre of the State University of Groningen proved that archaeological research can enrich and even correct historical research. No inhabitation took place before and after Smeerenburg. Archaeological and historical data could be confronted because written and iconographical sources on this settlement were available as well.Historical facts: To defy the English at the whale-fishery in the waters of Spitsbergen merchants from different Dutch ports founded the North Company (1614-1642) thus forming a chamber-syndicate of enterprises. Try-houses were built to boil the whale's blubber to train-oil. The settlement Smeerenburg on Amsterdam Island consisted of several of these try-houses. After the discovery of Jan Mayen (1614) the centre of gravity of Dutch whale-fishery soon moved to this island.After a difficult, less lucrative period from 1625 to 1630 the North Company declined quickly. From 1642 on whale-fishery was taken over by small-scaled shipping companies. Although the Dutch hunted whales in the waters of Spitsbergen till deep into the 18th century the try-houses were left around 1600 because of the increase of ice years, which radically shortened the labour season.According to a printed map the try-house of the Chamber of Hoorn (1625) was situated on the western side of Smeerenburg. Written sources suggest decreasing employment after 1642. An iconographical source offers a representation of the try-house with double round brick ovens, wooden chimneys and four simple wooden houses, two of these buildings having a storehouse.From 1625 on the Chamber of Hoorn sent one or two ships to the north every year hereby closely cooperating with the Chamber of Enkhuizen. About 40 men worked in the Spitsbergen try-houses. Lists of the cargo during the journey and an inventory of one of the try-houses inform us on the men's properties.Archaeological facts: Archaeological research defined the try-houses as a network of islands on the coast of Spitsbergen, which have been colonized by whalers who brought their own socio-historical environment. One could identify two phases of inhabitation at the try-house of the Chamber of Hoorn. Iconography confirms this development to semi-permanent wooden settlement but archaeological findings also indicate intensive usage up to 1650.The excavated house has been constructed in the Dutch way although in course of time the building was adapted to Arctic circumstances. Archaeologists could trace the technical development of the Dutch method of working up of the whale at the beginning of the 17th century, which method previously had been influenced by the Basques.Remainders of houses point at the presence of about 200 inhabitants on Smeerenburg, which is at variance with the supposed number from written sources. On the other hand written sources allow refined dating of artefacts. Many Dutch objects were found, while findings of iron objects indicate the presence of a blacksmith in the try-house archaeological research thus adding to written sources.Apart from data on nourishment a large quantity of shaped whalebone was found for the first time pointing to experiments with this new material in the try-house of the Chamber of Hoorn. Thus archaeological research provided for more insight into the enterprise's development and daily life in an Arctic station of whale-fishery. The confrontation of written and material sources resulted in correction of the 'historical reality' modify both the importance of the North Company to the total economy of the Republic and the Company's activities in the waters of Spitsbergen.